Komunitas dan Media Baru: Identitas Komunitas Keagamaan Diaspora dalam Media Baru - Adeni, Adeni (Universitas Merdeka Madiun, 2025)
This article aims to conduct a conceptual review of the identity of diaspora religious communities. This study uses a literature review approach, to map (1) minority religious identities in new media; (2) opportunities and possibilities for the formation of imagined communities for minority religious groups through new media; and (4) diaspora spaces for minority religious communities in new media. This study confirms that these digital religious communities are formed as “imagined religious communities,” which are an opposition to conventional religion. Those who join these digital communities usually come from various social pressures in real (physical) space. They are digitally formed with an orientation to produce and maintain ‘religious/belief’ identities more freely. This study contributes theoretically to strengthening the literature related to diaspora religious identities in digital space.